Application of radish pods in households and effect of their active components against different diseases: A review - Sana Noreen; Waseem Khalid; Madiha Khan Niazi; Miral Javed; Afifa Aziz; Awais Raza; Muhammad Zubair Khalid; Moses Vernonxious Madalitso Chamba (International Journal of Food Properties, 2023)
This review discusses the chemical composition of radish pods and their utilization and health perspective. Radish pods are green vegetables usually consumed in East Asia. Radish pods have gained much interest due to their high chemical composition and antioxidant activity. They contain various chemical compounds, including coumarins, phenols glucosinolates, antioxidants etc. In East Asia, radish pods are usually consumed in households and can also be used commercially as an additive ingredient. However, it can be used in the household as a vegetable, mixed vegetable and additive materials. Radish pods play an important role against cancer, hypertension, cardiovascular diseases, inflammation, and allergies via diverse pathways. It also acts as a hepatoprotective, platelet aggregation and immunity booster. Hence, the radish pods can be used in households for improvement of chronic disorders.